Peran Guru Pendidikan Agama Islam dalam Pembinaan Akhlak pada Anak Autis - Kosma Nengsi; Miswadi (GHAITSA : Islamic Education Journal, 2025)
This study aims to explore the role of Islamic Religious Education teachers in instilling religious values to autistic children, given that education for children with special needs has a different approach from education for children in general. The type of research used is a literature study with an Islamic religious education approach. The results showed that morals are an important element in Islamic education, and the role of Islamic Religious Education teachers is vital in shaping the morals of autistic children. The teacher functions as a director, controller, and guide in shaping the behavior of autistic children. Moral development in autistic children must be supported by comprehensive Islamic religious knowledge, as well as a correct understanding of faith and creed. It aims to develop basic human potential in order to have a good heart, mind and behavior. In conclusion, Islamic Religious Education teachers play a key role in guiding and directing the morals of autistic children, with the aim of helping children develop according to their age.